Pathway Enrichment Analysis of Microarray Data Fom Human Penis of Diabetic and Peyronie's Patients, in Comparison with Diabetic Rat Erectile Dysfunction Models. Issue 1 (25th November 2021) - Searl, Tim; Ohlander, Samuel; McVary, Kevin T.; Podlasek, Carol A.
ABSTRACT: Background: Erectile dysfunction (ED) is a debilitating medical condition in which current treatments are minimally effective in diabetic patients due to neuropathy of the cavernous nerve, a peripheral nerve that innervates the penis. Loss of innervation causes apoptosis of penile smooth muscle, remodeling of corpora cavernosa (penile erectile tissue) morphology, and ED. Aim: In this study, microarray and pathway analysis were used to obtain a global understanding of how signaling mechanisms are altered in diabetic patients and animal models as ED develops, in order to identify novel targets for disease management, and points of intervention for clinical therapy development. Methods and Outcomes: Human corpora cavernosal tissue was obtained from diabetic (n = 4) and Peyronie's (control, n = 3) patients that were undergoing prosthesis implant to treat ED, and BB/WOR diabetic (n = 5) and resistant (n = 5) rats. RNA was extracted using TRIzol, DNase treated, and purified by Qiagen mini kit. Microarray was performed using the Human Gene 2.0 ST Array. (i) Alterations in patient and diabetic rat pathway signaling were examined using several analytical tools (ShinyGO, Metascape, WebGestalt, STRING) and databases, (ii) Strengths/weaknesses of the different pathway analysis tools were compared, and (iii) Comparison of human and rat (BB/WOR and Streptozotocin) pathway analysis was performed. Two technical replicates were performed. P value (FDR) < .15 was used as threshold for differential expression. FDR < 0.05 was considered significant. Results: Microarray identified 182 differentially expressed protein-coding genes. Pathway analysis revealed similar enrichments with different analytical tools. Down regulated pathways include development, tubular structure, sprouting, cell death, ischemia, angiogenesis, transcription, second messengers, and stem cell differentiation. ED patients, who have diabetes, incur significant loss of normal regulatory processes required for repair and replacement of injured corpora cavernosal tissue. Combined with loss of apoptotic regulatory mechanisms, this results in significant architectural remodeling of the corpora cavernosa, and loss of regenerative capacity in the penis. Clinical Translation: This first report of microarray and pathway analysis in human corpora cavernosa, is critical for identification of novel pathways pertinent to ED and for validating animal models. Strengths and Limitations: The analysis of tissue specific gene expression profiles provides a means of understanding drivers of disease and identifying novel pathways for clinical intervention. Conclusion: Penis from diabetic ED patients lacks capacity for maintenance of corpora cavernosal architecture and regeneration, which are critical points for intervention for therapy development.